Development of LKPD Based on Contextual Teaching and Learning in Social Studies Lessons to Improve the Higher Level Thinking Skills of Grade IV Students of SDN Inpres Buncu - Zihan Maulani Masrun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This research aims to develop Contextual Teaching and Learning (CTL)-based Student Worksheets (LKPD) in science subjects to improve the SDN Inpres Buncu's grade IV pupils' Higher Order Thinking Skills (HOTS). The ADDIE model, which comprises the phases of analysis, design, development, implementation, and evaluation, is used in this development research. The study participants included expert validators (materials, media) and class IV students. Questionnaires for expert validation, instructor response, and student response are examples of data gathering tools. lifts, learning implementation observation sheets and test sheets. The validation results showed that LKPD was very feasible with a percentage of material experts of 91% and media experts of 92% indicating that LKPD was under the